Некоторые сведения о самках морских котиков (Mammalia, Otariidae) о. Беринга - Нестеров, Г.А.; Чугунков, Д.И. (Вестник зоологии, 1978)
The main task of the research carried out in October 1972 on the North and North-Western lies of the Bering island was to determine age composition of females, physiological state of their genitalia and mammary glands and degree of female migration from different stocks.